Salvia wixarika (Lamiaceae), a new species from Jalisco, Mexico, and novelties on Mexican Salvia with white corollas - González-Gallegos, Jesús Guadalupe; López-Enríquez, Irma Lorena (Phytotaxa, 2016)
The new species Salvia wixarika from Sierra Madre Occidental region (northern Jalisco, Mexico) is here described and illustrated. This is one of the few Mexican species characterized by having corollas entirely white. It is morphologically related to S. sphacelifolia but differs by the absence of glandular-capitate hairs, leaf shape, floral bract length, pedicel length, number of veins in the upper calyx lip, filament length, connective and style length. It is also similar to S. collinsii but differs in size and duration of floral bracts, pedicel length, calyx width, corolla length, lower lip size, filament length, connective length, theca and style length. Additionally, the updated descriptions of S. collinsii and S. sphacelifolia are provided.